The influence of socioeconomic status and birth weight on blood pressure of Indonesian pre-pubertal children - Madarina Julia; M M van Weissenburch; HA Delemarrevan de Waal; Achmad Surjono (Paediatrica Indonesiana, 2007)
Background It has been shown that elevated blood pressure (BP)in childhood contributes to the development of coronary arterydisease, cerebrovascular accidents, heart failure, and renal failurein adults. There is also evidence of some correlations betweenchildhood BP and BP in adulthood. Obesity as well as low birthweight are a risk factors for elevated BP, both in children and inadults. Most epidemiological studies have also shown arelationship between high BP and socioeconomic status (SES).Objective To assess the influence of socioeconomic status andbirth weight on blood pressure of school-aged prepubertal childrenliving in Indonesia.Methods A cross-sectional survey on 2922 school-agedprepubertal children from the rural, poorurban and nonpoor urbancommunities was performed. Data on age, sex, stature, BMI, birthweight, systolic and diastolic BP were collected from all children.Results Overall and within every socioeconomic status group,blood pressures were positively associated with stature and bodymass index (BMI). Children from poor-socioeconomic families,i.e. rural and poor urban, had significantly lower height and BMI,and hence, in the unadjusted analyses, poor socioeconomic statuswas associated with lower systolic and diastolic BP. However, afteradjustment for age, sex, stature and BMI, rural children were foundto have significantly higher systolic BP compared to nonpoor urbanchildren, with regression coefficient (95% CI) of 1.19(0.42 to1.96). Birth weight was not associated with blood pressure inchildhood.Conclusion This study indicated that for a given stature and BMI,poor children had a higher systolic BP